Fifty Major Thinkers on Education From Confucius to Dewey - Palmer-Cooper, Joy A. (London Routledge, 2001)
In this unique work some of today''s greatest educators present concise, accessible summaries of the great educators of the past. Each essay gives key biographical information, an outline of the individual's principal achievements and activities, an ass
Keywords: Education -- Philosophy -- History. Educators -- Biography. Education -- History. BIOGRAPHY & AUTOBIOGRAPHY -- Educators. Education. Education -- Philosophy. Educators. Biografie Erziehungsphilosophie Geschichte Pädagoge.